Hydraulically operated palm oil loader system design as fresh fruit bunch collector - S. Sarip; M. A. Suhot; H. M. Kaidi; M. F. Mohd Noor; S. Abdul Aziz; N. A. Bani; M. S. Noorazizi (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Palm oil is one of the main agricultural contributors to Malaysia’s Gross Domestic Product (GDP). Although commercial palm oil plantations have flourished in Malaysia for decades, there is still room for improvement especially in minimizing manpower load and developing efficient machinery to improve the various processes involved in the palm oil industry from estate to the mills. This paper presents a modified towable backhoe to assist in the Fresh Fruit Bunch (FFB) collecting process as an effort to save time. The main objective of this study is to design a machine that can be used by smallholders of oil palm in order to help speed up the work process. With a boom extension and an innovative grabber, the pressure needed to operate the hydraulic system was analyzed to ensure the towable backhoe functioned effectively and fulfilled its objectives. From the calculations done, the maximum pressure that the system can supply is 31.28 MPa which is higher than the 11 MPa minimum required for the hydraulic system to operate.